Law Enforcement in Uncovering the Perpetrators of Fraud Crimes Committed by BRI Link Employees - Elisabeth Saragih; Muhammad Arif Sahlepi; Muhammad Azhali Siregar (Journal of Research in Social Science and Humanities, 2025)
Law enforcement is a crucial element in maintaining order and justice within society, particularly in addressing increasingly complex fraud crimes involving various parties, including financial institution employees. Fraud committed by BRI Link employees has serious implications for customer trust and the stability of the banking system. This study aims to examine the mechanisms of law enforcement in uncovering the perpetrators of fraud crimes committed by BRI Link employees and to identify the obstacles encountered in the enforcement process. The research employs a normative juridical method with statutory and case approaches. The study finds that the ambiguous legal status of BRI Link agents constitutes a major obstacle to law enforcement. The investigation process often faces challenges such as insufficient physical evidence, the dominance of digital evidence, and limited access to bank data. The complexity of technology and fragmented regulations further hinder investigations. Based on normative jurisprudence, Article 378 of the Indonesian Criminal Code (KUHP) serves as the main legal basis for prosecuting fraud crimes, while the Banking Act and Consumer Protection Act govern the rights and responsibilities of victims. To enhance the effectiveness of law enforcement, regulatory harmonization, investigator capacity building, and inter-institutional cooperation are essential